1994
DOI: 10.1088/0953-8984/6/28/026
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoresistance in sputtered (Co70Fe30)xAg1-xheterogeneous alloys

Abstract: We report the structural, magnetic and transport properties of (Co70Fe30)xAg1-x heterogeneous alloys, with x varying between 27 and 47 at.%. The samples were prepared by DC triode sputtering at room temperature (RT) and liquid-nitrogen temperature. Annealing processes lead to phase segregation and grain growth, resulting in the formation of small and compact Co70Fe30 precipitates. The resulting evolution of the magnetic properties has been investigated by SQUID magnetometry, Mossbauer spectroscopy and ferromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Even for this concentration, the FC curve does not become completely flat, as has been observed for similar concentrations in Co-SiO 2 granular films 15 and in metallic CoFe-Ag alloys. 31,32 This feature seems to indicate the absence of strong magnetic interactions between particles for Co concentrations up to about x = 0.30, as may also be deduced from the relatively small values of . Sankar et al 33 reported = −29 K and = −34 K for Co-SiO 2 granular films with x = 0.32 and x = 0.41, respectively.…”
Section: A DC Susceptibilitymentioning
confidence: 51%
“…Even for this concentration, the FC curve does not become completely flat, as has been observed for similar concentrations in Co-SiO 2 granular films 15 and in metallic CoFe-Ag alloys. 31,32 This feature seems to indicate the absence of strong magnetic interactions between particles for Co concentrations up to about x = 0.30, as may also be deduced from the relatively small values of . Sankar et al 33 reported = −29 K and = −34 K for Co-SiO 2 granular films with x = 0.32 and x = 0.41, respectively.…”
Section: A DC Susceptibilitymentioning
confidence: 51%
“…Below x v ϳ0.20, annealed samples display the typical features of a granular solid constituted by a random distribution of nanometric CoFe particles within the Cu matrix. 5,12,13 The maximum magnetoresistance observed in this family is about 20% at low temperature (Tϭ20 K and Hϭ10 kOe) for an x v ϭ0.16 sample annealed at 600°C. The change in magnetoresistance is defined as,…”
Section: Transport Propertiesmentioning
confidence: 83%
“…Fe was added to Co ͑about 5-10 at.%͒ in the classical CoCu GMR system as a minor FM component, in order to increase the GMR effect as previously reported, 5 by increasing the magnetic moment of the particles. Although the physical microstructure is almost the same for all the as-cast samples below the percolation threshold, magnetic and magnetotransport properties change dramatically with x v .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In particular, systems with Fe 30 Co 70 / Cu alloy compositions exhibited one of the largest magnetoresistance amplitude reported so far at 4 K in granular alloys. 12,13 Nowadays, Fe x Co 1−x systems are also used in magnetic tunnel junctions with spin-valve architecture such as magnetic tunnel transistor devices. 14 In order to understand the magnetic behavior of the Fe 30 Co 70 / Cu multilayers under ion irradiation it is necessary first to investigate the structural evolution.…”
Section: Introductionmentioning
confidence: 99%